Fundamental properties of single O stars in the MiMeS survey. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Martins, F.; Hervé, A.; Bouret, J.-C.; Marcolino, W. L. F.; Wade, G. A.; Neiner, C.; Alecian, E.; ,
Abstract: We present preliminary results of the determination of fundamental parameters of single O-type stars in the MiMeS survey. We present the sample and we focus on surface CNO abundances, showing how they change as stars evolve off the zero-age main sequence.